1992
DOI: 10.1246/bcsj.65.965
|View full text |Cite
|
Sign up to set email alerts
|

Racemization of Optically Active Aromatic N-Acetylamino Acids and Asymmetric Transformation of N-Acetyl-2-(4-hydroxyphenyl)glycine via Salt Formation with Optically Active α-Methylbenzylamine

Abstract: The racemization rates of N-acetyl-(S)-tyrosine, N-acetyl-(S)-phenylalanine, N-acetyl-(R)-2-(4-hydroxyphenyl)glycine [(R)-AcHpg], N-acetyl-(R)-2-phenylglycine, and N-acetyl-(S)-alanine were measured by use of (RS)-α-methylbenzylamine [(RS)-MBA] as a base-catalyst. The first-order rate constant for racemization tended to increase with an increase in the polar substituent constant of the N-acetylamino acid side chain. The racemization appeared to be subject to the inductive effect by the side chain. An asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…20 p-Hydroxyphenylglycine 43 has attracted special attention from various groups, due to its utility as a side chain in semisynthetic penicillins and cephalosporins such as amoxicillin, cefadroxil, cefatrizine, cefaparole, and cefoperazon. In a systematic study Shiraiwa and co-workers 89 found that the rate of racemization of N-acetyl-amino acids increases proportionally with Taft's polar substituent constant (σ*) of the amino acid side chain and also with increasing amounts of the (R)-R-methylbenzylamine (R*NH 2 ) resolving agent. On this basis they developed a CIDT in which racemic N-acetyl-4-hydroxyphenylglycine 42 is converted in 95% yield to the (R,R)-salt (90-93% de) via heating with at least a 5-fold excess of the amine in a 5:1 mixture of cumene and 1-hexanol at reflux (150 °C) for 3 h (Scheme 25).…”
Section: Amino Acids and Related Compoundsmentioning
confidence: 99%
“…20 p-Hydroxyphenylglycine 43 has attracted special attention from various groups, due to its utility as a side chain in semisynthetic penicillins and cephalosporins such as amoxicillin, cefadroxil, cefatrizine, cefaparole, and cefoperazon. In a systematic study Shiraiwa and co-workers 89 found that the rate of racemization of N-acetyl-amino acids increases proportionally with Taft's polar substituent constant (σ*) of the amino acid side chain and also with increasing amounts of the (R)-R-methylbenzylamine (R*NH 2 ) resolving agent. On this basis they developed a CIDT in which racemic N-acetyl-4-hydroxyphenylglycine 42 is converted in 95% yield to the (R,R)-salt (90-93% de) via heating with at least a 5-fold excess of the amine in a 5:1 mixture of cumene and 1-hexanol at reflux (150 °C) for 3 h (Scheme 25).…”
Section: Amino Acids and Related Compoundsmentioning
confidence: 99%
“…Investigations of the reaction kinetics of free amino acids in buffered aqueous solutions indicate that reversible first-order rate laws are valid; however, some peptides and proteins have more complex kinetics . Rate constants for racemization have been measured for several molecules, with additional values cited in the review by Bada . Typical values of the rate constant k r range from 1 × 10 -4 to 1 × 10 -1 s -1 .…”
Section: Chiral Crystallization and Asymmetric Transformationmentioning
confidence: 99%